Winning through Cross-Cutting : Breaking Down IFC Silos to Promote Access to Finance in Rural Bangladesh - Kamal, Sayed Tarek; Haque, Mekhola; Zaman, Zaki Uz (World Bank, Washington, DC, 2012)
In an increasingly congested market for financial institutions in the major cities of Bangladesh, United Leasing Company (ULC), an International Finance Corporation (IFC) partner financial institution, decided to go where other such institutions were not yet focusing, rural Bangladesh. The smart lesson describes how IFC South Asia Enterprise Development Facility (SEDF) was able to leverage internal expertise and help ULC take a first-mover position and access viable businesses in rural Bangladesh.